Influence of carbon nanotubes in gel electrolyte on photovoltaic performance of ZnO dye-sensitized solar cells - Natthorn Khongchareon (2018)
In this work, the poly(ethylene glycol) (PEG) gel polymer electrolyte was used to replace the liquid electrolyte in dye-sensitized solar cells (DSSCs) in order to overcome the issues of evaporation, leak of liquid, and stability. However, the PEG gel polymer electrolyte-ZnO based cells have low current density and fill factor. Then, the effect of addition of multi-walled carbon nanotubes (MWCNTs) in different wt% into the PEG gel polymer electrolyte was also investigated. Current density-voltage characteristics and electroch emical impedance spectroscopy showed that use of the MWCNTs with the PEG gel polymer electrolyte increases current density and fill factor. Highest efficiency of 0.75% was achieved with 5 wt% of the MWCNTs in the PEG gel polymer electrolyte. The enhancement of efficiency can be attributed to the suppression of charge transfer resistance at the ZnO photoelectrode/electrolyte interface, whereas the proper introduction of MWCNTs effectively decreases the charge recombination as confirmed by electrochemical impedance spectra. In case of stability, the devices sustained for 1006 h also maintained over 85% of its initial performance. © 2013 Elsevier Ltd. All rights reserved.